A prospective multicenter pilot study of HIV‐positive deceased donor to HIV‐positive recipient kidney transplantation: HOPE in action. Issue 5 (8th August 2020) - Durand, Christine M.; Zhang, Wanying; Brown, Diane M.; Yu, Sile; Desai, Niraj; Redd, Andrew D.; Bagnasco, Serena M.; Naqvi, Fizza F.; Seaman, Shanti; Doby, Brianna L.; Ostrander, Darin; Bowring, Mary Grace; et al.
Abstract : HIV‐positive donor to HIV‐positive recipient (HIV D+/R+) transplantation is permitted in the United States under the HIV Organ Policy Equity Act. To explore safety and the risk attributable to an HIV+ donor, we performed a prospective multicenter pilot study comparing HIV D+/R+ vs HIV‐negative donor to HIV+ recipient (HIV D−/R+) kidney transplantation (KT). From 3/2016 to 7/2019 at 14 centers, there were 75 HIV+ KTs: 25 D+ and 50 D− (22 recipients from D− with false positive HIV tests). Median follow‐up was 1.7 years. There were no deaths nor differences in 1‐year graft survival (91% D+ vs 92% D−, P = .9), 1‐year mean estimated glomerular filtration rate (63 mL/min D+ vs 57 mL/min D−, P = .31), HIV breakthrough (4% D+ vs 6% D−, P > .99), infectious hospitalizations (28% vs 26%, P = .85), or opportunistic infections (16% vs 12%, P = .72). One‐year rejection was higher for D+ recipients (50% vs 29%, HR: 1.83, 95% CI 0.84‐3.95, P = .13) but did not reach statistical significance; rejection was lower with lymphocyte‐depleting induction (21% vs 44%, HR: 0.33, 95% CI 0.21‐0.87, P = .03). In this multicenter pilot study directly comparing HIV D+/R+ with HIV D−/R+ KT, overall transplant and HIV outcomes were excellent; a trend toward higher rejection with D+ raises concerns that merit further investigation. Abstract : In this multicenter HOPE Act study of 75 HIV‐positive kidney transplant recipients, patient survival, graft survival, and HIV‐related complications are similar between those receiving kidneys from HIV‐positive and HIV‐negative deceased donors, but a trend toward higher rejection with HIV‐positive donors merits surveillance and careful tailoring of immunosuppression. See the editorial from Montero et al on page 1683 .